Pengaruh Budaya Organisasi, Disiplin Kerja Dan Kualitas Pelayanan Pegawai Terhadap Kepuasan Masyarakat Pada Kantor Kelurahan Desa Labuhan Ratu VII Kecamatan Labuhan Ratu Kabupaten Lampung Timur - Nani Septiana; Durotun Nasikah; Nurul Zulaiha (Universitas Muhammadiyah Metro, 2024)
Based on the results of separate interviews by researchers with residents or communities whoprovide services at the village office, it was found that the booming e-KTP problem at thattime this problem was from the center because of the limited forms, each village office onlygot a few blanks, so the attitude taken by service employees Urgent people take precedence,not according to people who have previously made e-KTPs, so people feel unfair withdecisions like this every community who comes and asks about their e-KTP is still in theprocess with a span of months. This study aims to determine the influence of organizationalculture, work discipline, service quality on community satisfaction at the Labuhan Ratu VIIVillage Office, Labuhan Ratu District, East Lampung. This type of research is a quantitativestudy using the Incidental Sampling method, namely the technique of determining the samplebased on chance, namely 80 samples. The data used is secondary data distribution ofquestionnaires in the form of a list of questions with several alternative answers forrespondents. The statistical test used to test the hypothesis is multiple linear regressionanalysis and tested using the statistical packages for the social science (SPSS) version 21program. Based on the results of statistical tests indicate that organizational culture, workdiscipline, service quality have a positive and significant influence on people's satisfaction